Preclinical Assessment of MEK Inhibitors for Malignant Peripheral Nerve Sheath Tumors Reveals Differences in Efficacy and Adaptive Response - Gu, Yihui; Wang, Wei; Li, Yuehua; Li, Haibo; Guo, Zizhen; Wei, Chengjiang; Long, Manmei; Chung, Manhon; Aimaier, Rehanguli; Li, Qingfeng; Wang, Zhichao (Frontiers in Oncology, 2022)
Malignant peripheral nerve sheath tumors (MPNSTs) are rare soft-tissue sarcomas refractory to standard therapies. Inactivation of NF1 and subsequent upregulation of RAS/RAF/MEK/ERK signaling exist in the majority of MPNSTs. However, the lack of preclinical assessment of MEK inhibitors in MPNSTs hinders the clinical application as well as the development of combination therapy. To guide further clinical studies, we evaluated different MEK inhibitors in terms of efficacy, safety, and mechanism of adaptive response in treating MPNSTs. Using a MPNST tissue microarray, we found that p-ERK could serve as a biomarker for predicting the prognosis of MPNST patients as well as an effective therapeutic target. Through in vitro and in vivo experiments, we identified trametinib as the most potent MEK inhibitor for the treatment of MPNSTs. Mechanistically, reduced reactivation of the MAPK pathway and compensatory activation of the parallel pathways contributed to better efficacy. Our results provide basis for the further clinical application of MEK inhibitors as single agents or combinational therapies.